Sleep apnoea and telemonitoring: The patient and healthcare professional perspective (Breathe (Sheff), 2015)
I started experiencing symptoms of extreme tiredness and severe lethargy about 18 years ago, a short while after an angina attack. I thought the symptoms were related to my angina and I did not immediately seek help.